New sesquiterpene lactones from Inula oculus-christi L. (September 2017) - Trendafilova, Antoaneta; Ivanova, Victoria; Todorova, Milka; Aneva, Ina
Graphical abstract: Highlights: The sesquiterpene lactone profile of Inula oculus-christi L. was studied. Gaillardin, pulchellins C and E, and four new sesquiterpene lactones were isolated. The structures were determined on the basis of NMR spectroscopy and HRESIMS. Abstract: Investigation of the aerial parts of Inula oculus-christi L. led to the identification of four new sesquiterpene lactones: an eudesmanolide (4α, 15α-epoxypulchellin E) and three guaianolides (2α-acetoxy-4α, 9β-dihydroxy-1β-guaia-11(13), 10(14)-dien-12, 8α-olide, 9β, 10β-epoxygaillardin, 9α, 10α-epoxy-2- epi -gaillardin), in addition to the known gaillardin, pulchellin E, pulchellin C and 3- O -palmitates of 16β-hydroxylupeol, 16β-hydroxy-β-amyrin, and faradiol. The structures of all compounds have been elucidated on the basis of their spectral data.